An aerobe exercise intervention for optimizing metabolic, cardiovascular and immune status: protocol of an intervention study with a multi-systemic approach for women with unexplained recurrent pregnancy loss - Habets, Denise; Gurbanova, Aysel; Lombardi, Amber; Al-Nasiry, Salwan; Spaanderman, Marc; van der Molen, Renate; Wieten, Lotte; Meuleman, Tess (Frontiers in Medicine, 2025)
Women confronted with recurrent pregnancy loss (RPL) are often desperately searching for a possible explanation and hoping they will someday fulfill a healthy pregnancy. Unfortunately, in more than 50% of these women no cause for their losses can be identified after clinical investigations and therefore clinicians have no treatment options to help these women. Although adaptations in several systems such as the metabolic, the cardiovascular, and the immune system are highly important to support early pregnancy, especially the contribution of a specific subset of immune cells in the uterus known as CD56bright Natural Killer (NK) cells has gained a lot of interest, investigating separate RPL associated factors might not be the way forward. Moreover, a readily available and non-invasive exercise intervention might optimize all systems simultaneously, reducing metabolic, cardiovascular and immunological risk factors contributing to RPL. Therefore, we propose an aerobe exercise intervention and study the influence on the cardiovascular, the metabolic, and the immune system, with a particular focus on endometrial CD56bright NK cells, in women with unexplained RPL. In this exercise intervention study, women with unexplained RPL will receive two questionnaires to assess baseline characteristics. Moreover, they will receive (1) an immunological assessment (by sampling menstrual blood, peripheral blood and a vaginal swab) (2) an assessment of the cardiovascular system (by transvaginal ultrasound to assess uterine artery perfusion, by measuring hemodynamic and autonomic nerve system responses during a tilt test and by maximum stress test on a cycle ergometer) and (3) a metabolic assessment (by sampling peripheral blood, urine and by measuring body characteristics) before and after intervention. The intervention consists of 12-weeks moderate exercise training based on 50–65% of heart rate reserve. One year after the end of the intervention women will receive a final questionnaire regarding possible subsequent pregnancy outcome. This clinical trial with a multi-systemic approach can not only provide new insights by studying contribution and associations of the immune system, the cardiovascular system and the metabolic system in women with unexplained RPL, it also can support shared decision-making between clinicians and patients by evaluating the importance of a ready available exercise intervention strategy.